Assessment for varicella zoster virus in patients newly suspected of having giant cell arteritis. (27th November 2019) - Sammel, Anthony M; Smith, Susan; Nguyen, Katherine; Laurent, Rodger; Brewer, Janice; Hall, Nathan; Little, Christopher B
Abstract: Objectives: There is uncertainty if varicella zoster virus (VZV) triggers GCA. This is based on discordant reports of VZV detection in GCA temporal artery biopsies. We conducted a multimodal evaluation for VZV in the inception Giant Cell Arteritis and PET Scan (GAPS) cohort. Methods: Consecutive patients who underwent temporal artery biopsy for suspected GCA were clinically reviewed for active and past VZV infection and followed for 6 months. Serum was tested for VZV IgM and IgG. Temporal artery biopsy (TAB) sections were stained for VZV antigen using the VZV Mouse Cocktail Antibody (Cell Marque, Rocklin, CA, USA). A selection of GCA and control tissues were stained with the VZV gE antibody (Santa Cruz Biotechnology, Dallas, TX, USA), which was used in previous studies. Results: A total of 58 patients met inclusion criteria, 12 (21%) had biopsy-positive GCA and 20 had clinically positive GCA. None had herpes zoster at enrolment and only one patient developed a VZV clinical syndrome (zoster ophthalmicus) on follow-up. There was no difference in VZV exposure between GCA and non-GCA patients. None of the 53 patients who had VZV serology collected had positive VZV IgM antibodies. VZV antigen was not convincingly demonstrated in any of the TAB specimens; 57 TABs stained negative and 1 stained equivocally positive. The Santa Cruz Biotechnology VZV antibody exhibited positive staining in a range of negative control tissues, questioning its specificity for VZV antigen. Conclusion: The absence of active infection markers argues against VZV reactivation being the trigger for GCA. Non-specific immunohistochemistry staining may account for positive findings in previous studies.